F tacheodispersion. Issue 10 (October 1993) - Chroni, E; Panayiotopoulos, C P
Abstract : F tacheodispersion is defined as the distribution of the conduction velocities of individual or small groups of nerve fibres estimated from significant numbers of consecutively recorded F waves. The ulnar and peroneal nerves in 18 healthy subjects were studied using this method and histograms of motor fibre conduction velocities for the control nerves were created. F tacheodispersion was applied in nine patients with neuropathies and radiculopathies selected on the basis that at least one nerve was 'normal' as measured by conventional techniques (M response, F wave minimum latency to height). In the patient group it was demonstrated that a significant proportion of motor nerve fibres had F tacheodispersion conduction velocities below normal limits despite normal conventional findings. It is concluded that F tacheodispersion should be considered in routine neurophysiological investigation when conventional methods had failed to reveal a suspected nerve lesion.